ANALISIS TINGKAT KETERCUKUPAN JALUR HIJAU JALAN DI KECAMATAN PADANG BARAT KOTA PADANG - Sri Ayu Novriawati; Endah Purwaningsih (JURNAL BUANA, 2020)
Analysis of the level of adequacy of the road green lanes is carried out in Padang Barat Sub-district, Padang City. The research aims to determine the distribution of road green lanes in Padang Barat Sub-district, determine the aqequacy level of road green lanes in Padang Barat Sub-district and find out the green lane plant recommendations on roads in the Padang Barat Sub-district. In analyzing is done by remote sensing methods and geographic information system.The method for calculating the level of availability of road green lanes is scoring and overlays. The result of the research obtained the distribution of road green lanes in Padang Barat Sub-district covering an area of 84.924,59 m2. The level of adequacy of the green lane of the road in the Padang Barat Sub-district is, 5 roads are included in the inadequate category, 22 roads are in the less adequate category and 19 roads are in the adequate category. The recommended plants in the study area are kiara payung plants (Filicium decipiens) that function as shade plants, absorbing air pollution and as a noise absorber. In addition to kiara payung plants, tanjung plants (Mimusops elengi) have very high resistance to cement dust pollution.